"Putting things in context": Literal and discourse approaches to comprehension assessment - Paul, R. (Seminars in Speech and Language, 2000)
Research on receptive language development in typical children, especially as explicated in a classic paper by Robin Chapman, is reviewed. These findings raise three challenges for clinicians assessing comprehension in children with language disorders: (1) contrary to popular wisdom, comprehension does not always precede production in a simple step-by-step way; (2) comprehension is a private event; indicators of comprehension must be used to assess it, and these indicators can be misleading; and (3) children with subtle comprehension deficits may do well on standardized tests that are not sensitive to their difficulties with real-time discourse. Some strategies for addressing these challenges, as well as a framework for assessing comprehension, are offered.
Keywords: *Child Language; *Cognition; *Language Tests; *Verbal Behavior; Child Language; Child, Preschool; Cognition; Comprehension assessment; Comprehension deficits; Comprehension stages; Discourse comprehension; Humans; Language Tests; Verbal Behavior; article; cognition; dept.cmd; human; language development; language test; preschool child; verbal behavior